Social Media and Elections: Reviewing the Use of Social Media in Election Contests during 2016-2022 – A Systematic Review and Bibliometric Analysis - Azizah, Nur; Rizki Eka Putra, Nur; Achmada Shaka Ramadhan, Nur (Universitas Pancasakti Tegal, 2025)
Social media has taken an important role and become one of the pillars in today's digital age democracy. There have been many articles produced in journals that analyze the study use of social media platforms in the context of elections in various countries. This study aims to create a previously generated research map from Scopus indexed journals on the development of social media used users in the general election from 2016 to 2022. The study was analyzed using bibliometrics, based on 533 Scopus articles. Descriptive statistical methods are used to be able to explore the author's network and the country of origin of the article using the Vosviewer application. This research has succeeded in providing an overview of the increase in the number of articles every year after elections in various countries. Based on the number of articles reviewed, the author who produces the most number of articles does not necessarily have the power of networking between authors. This research also provides an overview of the democratic system of government that has dominance in the use of social media in elections.